Definitive chemoradiation for primary oral cavity carcinoma: A single institution experience. Issue 7 (July 2015) - Scher, Eli D.; Romesser, Paul B.; Chen, Christine; Ho, Felix; Wuu, Yen; Sherman, Eric J.; Fury, Matthew G.; Wong, Richard J.; McBride, Sean; Lee, Nancy Y.; Riaz, Nadeem
Highlights We report our data for oral cavity cancer treated with chemotherapy and radiation. Actuarial 5-year overall survival was 15%. Kaplan–Meier 5-year locoregional control: 37%. Mucositis was the most common ⩾Grade 3 toxicity. Adequate and early multimodality treatment needed to improve outcomes.